2022
DOI: 10.1038/s41598-022-05037-w
|View full text |Cite|
|
Sign up to set email alerts
|

Low heart rate variability from 10-s electrocardiograms is associated with development of non-alcoholic fatty liver disease

Abstract: Reduced heart rate variability (HRV) is reflective of autonomic imbalance. However, its impact on non-alcoholic fatty liver disease (NAFLD) is unknown. We investigated the association between 10-s HRV and incident NAFLD. A cohort of 154,286 Korean adults with no NAFLD at baseline were followed up. 10-s electrocardiograms were used to estimate two time-domain HRV, the standard deviation of normal-to-normal intervals (SDNN) and the root mean square of successive differences in RR intervals (RMSSD). Hepatic steat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Another possible mechanism for the association between the prolonged QTc interval and NAFLD may be due to the autonomic imbalance that occurs in NAFLD [ 47 , 48 ]. The duration of the QT interval and QT dispersion is also known to be influenced by the autonomic nervous system [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism for the association between the prolonged QTc interval and NAFLD may be due to the autonomic imbalance that occurs in NAFLD [ 47 , 48 ]. The duration of the QT interval and QT dispersion is also known to be influenced by the autonomic nervous system [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are significant as SD NN and RMSSD are key indicators of HRV, reflecting different aspects of ANS function. Specifically, SD NN represents overall HRV and is considered a marker of both sympathetic and parasympathetic activity, while RMSSD primarily reflects parasympathetic (vagal) activity, which is linked to heart rate deceleration 36 . The autonomic adjustment observed suggests a phase of recovery from the acute stress of TGA, where the initial heightened autonomic activity diminishes as the body returns to a stable state 37 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Decreased heart rate variability reflects the imbalance in autonomic function. [ 12 ] Earlier studies have concluded that decreased HRV is directly associated with cardiometabolic risk factors leading to cardiovascular morbidity and mortality. [ 12 ] Impairment of HRV increases with increasing severity of liver disease as well as autonomic dysfunction in liver disease increases the risk of mortality rate fivefold.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Earlier studies have concluded that decreased HRV is directly associated with cardiometabolic risk factors leading to cardiovascular morbidity and mortality. [ 12 ] Impairment of HRV increases with increasing severity of liver disease as well as autonomic dysfunction in liver disease increases the risk of mortality rate fivefold. [ 10 ] LF and HF were found to be more in alcoholic fatty liver disease than the nonalcoholic fatty liver disease patients, but it was found to be under the normal range.…”
Section: Discussionmentioning
confidence: 99%